Regulation of Chitinase in Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) During Infection by Heliothis virescens ascovirus 3h (HvAV-3h) - He, Lei; Ou-Yang, Yi-Yi; Li, Ni; Chen, Ying; Liu, Shuang-Qing; Huang, Guo-Hua (Frontiers in Physiology, 2020)
Insect chitinases play essential roles in the molting and metamorphosis of insects. The virus, Heliothis virescens ascovirus 3h (HvAV-3h), can prolong the total duration of the larval stage in its host larvae. In this study, the molecular characterization and function of chitinase and chitin-binding domain (CBD) were analyzed in larvae of Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae). In detecting the chitinase activity of mock- infected and HvAV-3h infected larval whole bodies and four different larval tissues, the results showed that larval chitinase activity was significantly decreased at 48 hour post infection (hpi), and the chitinase activity of HvAV-3h infected larval fat body and cuticle was notably decreased at 144 and 168 hpi. The transcription level of S. exigua chitinase 7 (SeCHIT7) was down-regulated at the 6, 9, 12, 48, 72 and 96 hpi sample times, the S. exigua chitinase 11 (SeCHIT11) was down-regulated at 3-96 hpi, while both S. exigua chitinases (SeCHITs) were up-regulated at 120-168 hpi. Further tissue-specific detection of SeCHIT7 and SeCHIT11 transcription showed that SeCHIT7 was down-regulated at 144 and 168 hpi in the fat body and cuticle. SeCHIT11 was down-regulated at 168 hpi in the fat body, midgut and cuticle. Additionally, the transcription and expression of S. exigua chitin-binding domain (SeCBD) could not be detected in HvAV-3h infected larvae. The in vitro analyses of SeCHIT7N, SeCHIT11 and SeCBD showed that SeCHIT7N and SeCHIT11 were typical chitinases. Conversely, no chitinase activity was detected with SeCBD. SeCBD, however, could significantly increase the activity of SeCHIT7N and SeCHIT11. In conclusion, HvAV-3h not only interfered with the transcription and expression of SeCHITs, but also affected the normal transcription and expression of SeCBD, and, in doing so, influenced the host larval chitinase activity. The results will aid in providing a foundation for further studies on the pathogenesis of HvAV-3h.